Solid state bioconversion of food waste to compost and development of wastesoft (expert system) - Adebayo, Opatokun Suraj (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The rate at which solid wastes is generated across the globe is currently of great concern due to its social and institutional impacts on the environment and public health. The conventional method of wastes collection and its landfilling or incineration was observed to be unsustainable due to cost, pollution and the environmental effects. In this study, waste inventory was used to evaluate the effect of comingled and source separated solid wastes. The source separated organic wastes (FW and YT) were composted using selected fungal strains (Phanerochaete chrysosporium, Lentinus tigrinus, Aspergilus niger and Penicillium Spp) in a solid state bioconversion process. A software (WasteSoft) was also developed using Visual Studio to facilitate management and appropriate waste generated. The physicochemical properties of comingled waste (pH range of 3.83 – 4.17, COD range of 3431 – 96650 mg/l COD, EC range of 4.59 – 16.40 dS/m and BOD5/COD range of 6.7 × 10-3 – 9.82 × 10-2 mg/l) indicated it potential for material corrosion, greenhouse gas and primary leachate formation aside from the decrease in the economic value of the waste. The intercepted source separated food and yard trimmings wastes were composted using locally isolated fungal strains (Phanerochaete chrysosporium, Lentinus tigrinus, Aspergilus niger and Penicillium Spp) in two low technology adopted designs (open and close systems) in SSB process. Results obtained at p ≤ 0.05 after ten harvests indicated pH range of 6.03 – 7.05, DD range of 9.44 – 10.12% and C/N ratio range of 16.99 – 18.20% for the open systems of composting. The closed system indicated relatively lower yield values of percentage decrease in C/N ratio range of 8.60 – 13.38% and DD range of 6.42 – 7.57% at pH range of 5.68 – 6.37. Toxicity and stability of the compost were evaluated with germination index range of 43 – 105% and EC range of 2.57 – 3.17mS/dm for open system while the closed system indicated GI range of 46 – 132% and EC range of 2.72 – 2.95mS/dm for close system respectively. The decay coefficient was positive in the second order kinetics with R2 values closed to unity for both the opened and closed system. These parameters indicate the viability of the produced compost for large scale production especially with the C/N ratio < 25 and the significant GI value > 100 at harvest. WasteSoft heuristic strength facilitated waste management and provided hand on data and information about waste generated, therefore enhanced the appropriation of treatment measure using the IF- THEN decision algorithm to integrate its GUI and other acquired knowledge.